Motor Drive Coordination on a Belt Conveyor System Controlled by PLC at PT. Charoen Pokphand Indonesia - Rusly Herlangga (Journal of Emerging Innovations in Engineering, 2025)
This study investigates the coordination of drive motors in a Programmable Logic Controller (PLC)-based belt conveyor system used in the livestock feed packaging process at PT Charoen Pokphand Indonesia. The research addresses gaps in the integration of speed, power, and energy efficiency control in conveyor systems, especially in real-world industrial applications. Employing a quantitative experimental design, the study analyzes the impact of load variation on motor power, speed coordination, and overall system efficiency. Data were collected through direct experimentation on an industrial-scale conveyor equipped with Human-Machine Interface (HMI), Variable Frequency Drives (VFD), and real-time monitoring instruments. The results indicate that the conveyor system operates with high precision, maintaining minimal deviation between theoretical and actual speeds (within ±0.1%), and is supported by a finger robotic system that surpasses operational throughput requirements. The findings confirm that the integration of PLC and VFD enhances system flexibility, stability, and efficiency.